Modern Javanese directives: Balancing clarity and politeness in a high-context society - Emi Nursanti; Suhandano Suhandano; Sulistyowati Sulistyowati (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2026)
Javanese culture is widely characterized as a high-context society that prioritizes indirect communication to maintain social harmony. This study empirically tests this long-held assumption by examining the pragmatic structure of directive speech acts in contemporary data. Data were drawn from twenty short films produced by the Provincial Government of the Special Region of Yogyakarta and analyzed using a qualitative-dominant mixed-methods approach. Contrary to the classical paradigm, the analysis reveals a prevalent use of head act-oriented structures, indicating a preference for direct communication. This directness is frequently strategically combined with mitigating adjuncts, while the use of aggravating adjuncts is rare. Furthermore, a tendency toward simple pragmatic structures highlights a cultural emphasis on clarity and efficiency. These findings challenge the notion that indirectness is a necessary component of politeness. Instead, they suggest that in modern Javanese communication, directness and politeness operate as complementary, rather than contradictory, goals. Concise and direct utterances are not inherently impolite but are interpreted within the governing sociocultural and hierarchical context. This finding also indicates a sociolinguistic shift towards more direct and effective communication due to modernization.